丹戎布拉大学师范教育学院汉语专业 2020 届学生对 语气助词“吗 ”、 “呢 ”与 “吧 ”的掌握情况分析 - Dewi Lestari Lukman; Ina Ina; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe word modality particle is used to give additional meaning in grammar, this particle word is usually called a modality which is also commonly called a particle. Although there are differences in the use of these three words, students sometimes still don't understand in what situations they should use the words "Ma" "Ne" and "Ba".To understand the conditions of mastery and difficulty of students of the academic year 2020 Mandarin Language Education Study Program, Tanjungpura University on the modality particle words "Ma", "Ne" and "Ba", the author uses the Literature Study research method and the Evaluation method. The evaluation results show that the total percentage of mastery of the modal particle words “Ma”, “Ne” and “Ba”, in the 2020 students of the Mandarin Language Study Program, Tanjungpura University, namely: the percentage of correct answers for the word "Ma" is 71.18% the percentage of correct answers for the word "Ne" is 53.74% and the percentage of correct answers for the word "Ba" is 62.13%. From the results author, it can be seen that they have a better grasp of the use of the words "Ma" and "Ba" compared to the word "Ne".Keywords: Ma, Ne and Ba,Particles Modality,The Condition of Mastery